Exodus Politics : Civil Rights and Leadership in African American Literature and Culture - Patterson, Robert J. (Book collections on Project MUSE., 2013)
Using the term "exodus politics" to theorize the valorization of Black male leadership in the movement for civil rights, the author explores the ways in which the political strategies and ideologies of this movement paradoxically undermined the collective enfranchisement of Black people. He argues that by narrowly conceptualizing civil rights in only racial terms and relying solely on a male figure, conventional African American leadership, though frequently redemptive, can also erode the very goals of civil rights. The author turns to contemporary African American writers such as Ernest Gaines, Gayl Jones, Alice Walker, and Charles Johnson to show how they challenge the dominant models of civil rights leadership.